Analysis of orbit error effect on ultra-high space-ground two-way time comparison. Issue 1 (1st May 2022) - Guo, Yanming; Bai, Yan; Gao, Shuaihe; Zou, Decai; Chen, Xiaofeng; Wang, Rong; Liu, Yinhua; Gao, Yuping; Lu, Xiaochun
Abstract: In view of the characteristics of the low-orbit spacecraft's orbit, the influence of the low-orbit spacecraft's orbit error on the time comparison method based on tri-frequency is theoretically analyzed. With the simulation and test, validing the effectiveness of the precise two-way time comparison method, and the accuracy of the method can reach the order of ps-level. Furthermore, with the simulated data, the influence of orbit error on the ultra-high precise space-ground time comparison is analyzed. The results show that the percentage of orbit noise in the total orbit error has a great influence on the accuracy of time comparison. In order to achieve a link accuracy better than ps, the percentage of orbit noise should be kept within 5%.